The Rift and Continent‐Ocean Transition Structure Under the Tagus Abyssal Plain West of the Iberia. Issue 11 (18th November 2021) - Merino, I.; Ranero, C. R.; Prada, M.; Sallarès, V.; Grevemeyer, I.
Abstract: The West Iberia margin is the focus of intense research since the 1980s, with some of the most exemplary geophysical cross‐sections and drilling expeditions. Those data sets have been used to create conceptual models of rifting used as a template to interpret margins worldwide. We present two collocated ∼350 km long lines of multi‐channel seismic (MCS) streamer data and wide‐angle seismic (WAS) data collected across the Tagus Abyssal Plain (TAP). We use travel‐times of first arrivals identified at WAS and reflected seismic phases identified at both WAS and MCS records to jointly invert for the P wave velocity ( V p) distribution and the geometry of a sediment unconformity, the top of the basement, and the Moho boundary. The V p model shows that the TAP basement is more complex than previously inferred, presenting abrupt boundaries between five domains. Domain I under the foot of the slope and Domain III under the abyssal plain display V p values and gradients of thin continental crust. In between, Domain II displays a steep V p gradient and high V p values at shallow depth that support that basement is made of exhumed partly serpentinized mantle. Domain IV and Domain V, further oceanward, have oceanic crust V p structure. The new results support an unanticipated complex rift history during the initial separation of Iberia and America. We propose a geodynamic scenario characterized by two phases of extension separated by a jump of the locus of extension, caused by the northward propagation of the oceanic spreading center during the J‐anomaly formation, which terminated continental rifting. Plain Language Summary: The underground offshore of Western Iberia has been studied since the early 1980s to understand the mechanism that formed the North Atlantic Ocean around 200 million years ago. Some of the geophysical experiments carried on in this area have been used to created conceptual models that explain the opening of this region. Here, we present two new geophysical data sets to explore the Tagus Abyssal Plain (TAP), located in front of south Portugal, and to understand how the ocean opened up in this region. The integration of these two data sets allows us to create a seismic velocity model which decreases the uncertainty on the final interpretation regarding the origin of the TAP. The model from our study reveals that the TAP structure is more complex than previously proposed. We explain the new configuration by making the hypothesis that the ocean opens in two distinct and independent phases of extension. This is in contrast to the classical theories that states that the opening of this ocean took place progressively, in a unique episode of extension. Key Points: The first V p crustal model from joint travel‐time tomography of streamer and ocean bottom seismometer records of the Tagus Abyssal Plain Determination of the extent of two continental domains, an intervening exhumed mantle domain, and two distinct oceanic basement domains Opening occurred in two extension episodes: rifting leading to mantle exhumation and a seafloor spreading with the formation of oceanic crust